Development of auditory word processing in different task settings: a neurophysiological study on orthographic processes in reading and spelling. - Bakos, Sarolta; Schulte-Körne, Gerd; Moll, Kristina (Language, Cognition & Neuroscience, 2025)
The study compares electrophysiological correlates of auditory word processing between different orthography-related task settings and age groups (adults and children). After listening to a word stimulus, participants were asked to either spell the word (handwriting/spelling task) or to compare it to a visually presented word (word matching and orthographic decision tasks) or picture (baseline/picture matching task). The spelling task compared to the other tasks resulted in distinct electrophysiological patterns, starting after the first 320 ms (reflected in the N400 and LPC). These effects were similar both in adults and children. Furthermore, the spelling task resulted in stronger attentional focusing in both age groups, reflected in the early auditory evoked potentials (AEP) N1-P2 of the adult group and a distinctive centroparietal positivity (P300) in the child group. These results provide important insights into the development of spelling-related ERP components (N400, LPC) and AEP (P1-N1-P2).